2006
DOI: 10.1038/nn1669
|View full text |Cite
|
Sign up to set email alerts
|

Noise characteristics and prior expectations in human visual speed perception

Abstract: Human visual speed perception is qualitatively consistent with an optimal Bayesian observer that combines noisy measurements with a prior preference for lower speeds. Quantitative validation of this model, however, is difficult because the precise noise characteristics and prior expectations are unknown. Here, we present an augmented observer model that accounts for the variability of subjective responses in a speed discrimination task. This allows us to infer the shape of the prior probability as well as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

48
783
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 704 publications
(835 citation statements)
references
References 46 publications
48
783
4
Order By: Relevance
“…Moreover, the 184 speed component of our proposed mechanism suggests a neurally plausible way of encoding 185 perceptual priors in the same early cortical areas that provide sensory evidence [29,37].…”
mentioning
confidence: 80%
“…Moreover, the 184 speed component of our proposed mechanism suggests a neurally plausible way of encoding 185 perceptual priors in the same early cortical areas that provide sensory evidence [29,37].…”
mentioning
confidence: 80%
“…However, given that our participants will try to catch the ball, they might adapt the extrapolation process. Mrotek and Soechting (2007a) for instance showed that curvilinear target motion can be accurately extrapolated only if visual feedback of the post-occlusion path is provided, while de Lussanet et al (2001Lussanet et al ( , 2002 showed effects of target velocity in previous trials on the spatial features of hitting movements (see also Krauzlis and Adler 2001;Stocker and Simoncelli 2006). To anticipate, evidence for such adaptations during the blocked presentation of the occlusion conditions was indeed found.…”
Section: Introductionmentioning
confidence: 95%
“…Although one can always retrofit a statistical model to account for observed perceptual biases (as had been done for speed judgments) (17), the strong prediction of the probabilistic model of human perceptual inference is that observed biases (both to the mean and the preceding stimulus) will adapt to changes in the global statistics within a stimulus set. We tested this prediction for perceptual estimates of object speed used to plan hand movements to intercept a moving object (6,(14)(15)(16).…”
mentioning
confidence: 99%